1998
DOI: 10.1001/archopht.116.12.1629
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products in Age-related Macular Degeneration

Abstract: To investigate the localization of N ⑀-(carboxymethyl)lysine (CML), a component and major immunologic epitope of advanced glycation end products, in aged eyes and choroidal neovascular membranes (CNVMs) surgically excised from eyes with agerelated macular degeneration. Methods: Immunohistochemistry for CML was performed using 8 snap-frozen, surgically excised CNVMs. Twelve eyes from patients aged 69 to 82 years and 2 donor eyes, 1 each from a 23-week-old fetus and 21-yearold patient, without age-related macula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(97 citation statements)
references
References 22 publications
(30 reference statements)
2
93
0
2
Order By: Relevance
“…Further, CML is present in soft drusen and adjacent RPE cells before the development of choroidal neovascularization, but not in control eyes. 103 Although the implication of these findings warrants further exploration, it is consistent with an etiologic role for oxidative stress in the pathogenesis of AMD.…”
Section: Waste Products Of Oxidative Processes In Amdmentioning
confidence: 65%
“…Further, CML is present in soft drusen and adjacent RPE cells before the development of choroidal neovascularization, but not in control eyes. 103 Although the implication of these findings warrants further exploration, it is consistent with an etiologic role for oxidative stress in the pathogenesis of AMD.…”
Section: Waste Products Of Oxidative Processes In Amdmentioning
confidence: 65%
“…9 BrM and sub-RPE deposits contain glycosoaminoglycans [63][64][65][66] and advanced glycation end-products that could retain and modify lipoproteins, respectively. 67,68 Proteins associated with inflammation and complement activation are present in drusen. 69,70 ARMassociated choroidal neovascular membranes include macrophages and smooth muscle actin-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, these BM defects have been described as fragmentation or fracturing in association with calcification (81)(82)(83)(84)(85). Additional age-related changes in BM are typified by: 1) progressive thickening of the two collagenous layers; 2) modification and degeneration of collagen and elastin; 3) increased levels of advanced glycation end products, noncollagenous proteins and lipids; and 4) accumulation of several types of sub-RPE deposits (86)(87)(88)(89)(90)(91)(92)(93)(94)(95). It has also been suggested that the age-related abnormalities in BM eventually lead to photoreceptor degeneration as a result of increased hydrophobicity, reduced permeability, and impaired nutrient exchange between the choroid and the RPE.…”
Section: Morphological Correlates Of Early Amdmentioning
confidence: 99%